Potassium magnesium phosphate cementing material, raw materials, preparation method and application
By using sodium pyrophosphate, sodium pyrosulfate or thiourea as retarders in potassium magnesium phosphate gelling materials, the problem of inability to adjust the settling time and insufficient compressive flexural strength is solved, and high-performance repair materials that meet different engineering needs are achieved.
Patent Information
- Application Number
- CN202411636758.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-27
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-18
AI Technical Summary
The settling time of existing potassium magnesium phosphate gelling materials cannot be adjusted according to the needs of different engineering operations, and the flexural and compressive strength after coagulation is insufficient.
Sodium pyrophosphate, sodium pyrosulfate or thiourea are used as retarders. By adding these retarders to the raw materials of potassium magnesium phosphate gelling materials, the coagulation time is extended and the compressive and flexural strength after coagulation is ensured.
It realizes the setting time of potassium magnesium phosphate gelling materials according to different engineering operations needs, and meets the requirements of compressive and flexural strength after setting, and is suitable for repairing and protecting cement concrete structures.
Smart Images

Figure CN119638235A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of construction, and more specifically, to a potassium magnesium phosphate gelling material and raw materials, a preparation method and application thereof. Background Art
[0002] For engineering operations that are experiencing serious engineering hazards or are about to cause serious hazards, rapid filling and repair materials are often used to carry out emergency repairs on damaged structures.
[0003] Potassium magnesium phosphate cementitious material is a commonly used rapid filling and repair material. It is widely applicable and has the characteristics of rapid solidification, short time to reach normal operation, and high compatibility with the substrate. At present, retarders (such as borax) are often used to delay the setting time of potassium magnesium phosphate cementitious material. However, in engineering applications, the setting time of retarders required for different engineering operations can be adjusted according to actual needs, while meeting the flexural and compressive strengths after solidification.
[0004] Therefore, it is necessary to provide a retarder that can delay the setting time of potassium magnesium phosphate cementitious materials according to the requirements of different engineering operations and can ensure the flexural and compressive strength after setting. Summary of the invention
[0005] In view of this, the present application proposes a retarder and raw material, a preparation method and application of potassium magnesium phosphate gelling material.
[0006] A raw material for potassium magnesium phosphate gelling material, characterized in that, by weight, the raw material for the potassium magnesium phosphate gelling material comprises 200 parts of dead-burned magnesium oxide, 125 parts of potassium dihydrogen phosphate and 8 parts of a retarder;
[0007] Alternatively, the raw materials of the potassium magnesium phosphate gelling material include 100 parts of dead-burned magnesium oxide, 100 parts of potassium dihydrogen phosphate and 3 parts of retarder, in parts by weight;
[0008] Alternatively, the raw materials of the potassium magnesium phosphate gelling material include 250 parts of dead-burned magnesium oxide, 150 parts of potassium dihydrogen phosphate and 10 parts of retarder, by weight;
[0009] The retarder is sodium pyrophosphate, sodium pyrosulfate or thiourea, preferably sodium pyrophosphate.
[0010] In another aspect of the present invention, a potassium magnesium phosphate gelling material is provided, which comprises a raw material of a potassium magnesium phosphate gelling material and water. In parts by weight, the raw material comprises 180 parts to 240 parts of the raw material of the potassium magnesium phosphate gelling material and 60 parts to 120 parts of water. The raw material of the potassium magnesium phosphate gelling material is the raw material of the potassium magnesium phosphate gelling material according to claim 1. In an air-hardening environment, the setting time of the potassium magnesium phosphate gelling material is at least 8 minutes. The compressive strength of the potassium magnesium phosphate gelling material after setting for 3 days is at least 20 MPa, the compressive strength after setting for 28 days is at least 40 MPa, and the flexural strength is at least 6 MPa.
[0011] Another aspect of the present invention is a method for preparing a potassium magnesium phosphate gelling material, which comprises fully mixing the raw material of the potassium magnesium phosphate gelling material with water, or mixing a retarder with water, and then adding magnesium oxide and potassium dihydrogen phosphate and stirring to obtain the potassium magnesium phosphate gelling material, wherein: the raw material of the potassium magnesium phosphate gelling material is the raw material of the potassium magnesium phosphate gelling material mentioned above, and the retarder is the retarder mentioned above.
[0012] Another aspect of the present invention is an application of a potassium magnesium phosphate cementitious material, which is the application of the potassium magnesium phosphate cementitious material in repairing and / or protecting cement concrete material structures, and the potassium magnesium phosphate cementitious material is the potassium magnesium phosphate cementitious material mentioned above.
[0013] The retarder of the potassium magnesium phosphate gelling material of the present application can delay the setting time of the potassium magnesium phosphate gelling material and ensure the compressive strength of the potassium magnesium phosphate gelling material after setting.
[0014] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The accompanying drawings constituting a part of the present application are used to provide a further understanding of the present application, and the schematic implementation modes and descriptions of the present application are used to explain the present application. In the accompanying drawings:
[0016] Figure 1 This is a graph showing the activity test of dead-burned magnesium oxide using the acetic acid method in this application.
[0017] Figure 2 This is an analysis diagram of the dissolution, dispersion, bonding and crystallization mechanism of the potassium magnesium phosphate gelling material in this application.
[0018] Figure 3 It is the flexural strength of the potassium magnesium phosphate cementitious material when the sodium pyrophosphate in this application is used as a retarder.
[0019] Figure 4 It is the flexural strength of the potassium magnesium phosphate cementitious material when sodium pyrosulfate is used as a retarder in this application.
[0020] Figure 5 It is the flexural strength of the potassium magnesium phosphate cementitious material when thiourea is used as a retarder according to the present application.
[0021] Figure 6 It is the flexural strength of potassium magnesium phosphate cementitious material when borax is used as retarder according to the present application.
[0022] Figure 7 It is the compressive strength of the potassium magnesium phosphate cementitious material when the sodium pyrophosphate in this application is used as a retarder.
[0023] Figure 8 It is the compressive strength of the potassium magnesium phosphate cementitious material when sodium pyrosulfate is used as a retarder according to the present application.
[0024] Fig. 9 It is the compressive strength of the potassium magnesium phosphate cementitious material when thiourea is used as a retarder according to the present application.
[0025] Fig.10 It is the compressive strength of potassium magnesium phosphate cementitious material when borax is used as retarder according to the present application.
[0026] Fig.11 It is the setting time of the potassium magnesium phosphate cementitious material when sodium pyrophosphate is used as a retarder according to the present application.
[0027] Fig.12 It is the setting time of the potassium magnesium phosphate cementitious material when sodium pyrosulfate is used as a retarder according to the present application.
[0028] Fig.13 It is the setting time of potassium magnesium phosphate cementitious material when thiourea is used as retarder according to the present application.
[0029] Fig.14 It is the setting time of potassium magnesium phosphate cementitious material when borax is used as retarder according to the present application.
[0030] Fig.15 The microstructure of the potassium magnesium phosphate cementitious material when the retarder in Example 6 of the present application is sodium pyrophosphate.
[0031] Fig.16 The microstructure of the potassium magnesium phosphate cementitious material when the retarder in Example 6 of the present application is sodium pyrosulfate.
[0032] Fig.17 The microstructure of the potassium magnesium phosphate cementitious material when the retarder in Example 6 of the present application is thiourea.
[0033] Fig.18 The microstructure of the potassium magnesium phosphate gel material according to Comparative Example 4 in the present application.
[0034] Fig.19 It is the effect of sodium pyrophosphate on the pH of the hydration process of potassium magnesium phosphate gelling material.
[0035] Fig. 20 The figure shows the effect of sodium pyrophosphate on the amount of hydration products and hydration degree of potassium magnesium phosphate cementitious material, where (a) is the mass loss curve of MKPC, and (b) is the hydration product amount and hydration degree curve of MKPC.
[0036] Fig.21 It is the XRD diffraction pattern of sodium pyrophosphate modified potassium magnesium phosphate gelling material.
[0037] Fig. 22 This is a microstructure diagram of the sodium pyrophosphate modified potassium magnesium phosphate gelling material.
[0038] Fig.23 The effect of sodium pyrophosphate and borax on the pore structure of potassium magnesium phosphate cementitious materials. (a) Pore size distribution diagram, (b) cumulative pore volume diagram, (c) pore volume percentage diagram in different pore size intervals.
[0039] Fig.24 Effect of thiourea on pH of potassium magnesium phosphate cementitious material during hydration
[0040] Fig.25 The figure shows the effect of thiourea on the amount of hydration products and hydration degree of potassium magnesium phosphate cementitious material, where (a) is the mass loss curve of MKPC, and (b) is the hydration product amount and hydration degree curve of MKPC.
[0041] Fig.26 It is the XRD diffraction pattern of thiourea modified potassium magnesium phosphate gelling material.
[0042] Fig. 27 This is the microstructure diagram of thiourea modified potassium magnesium phosphate gelling material.
[0043] Fig.28 The effects of thiourea and borax on the pore structure of potassium magnesium phosphate gelling materials. (a) Pore size distribution diagram, (b) cumulative pore volume diagram, (c) pore volume percentage diagram in different pore size intervals.
[0044] Fig.29 The effect of thiourea and borax on the pore structure of potassium magnesium phosphate gelling material. (a) Pore size distribution diagram, (b) cumulative pore volume diagram, (c) pore volume percentage diagram in different pore size intervals. DETAILED DESCRIPTION
[0045] The technical solution of the present application will be described in detail below in conjunction with specific implementation methods.
[0046] The judgment standard for the setting time and strength of potassium magnesium phosphate cementitious materials in this application refers to the basic performance requirements of repair mortar in the national standard JC / T2381-2016.
[0047] Unless otherwise specified, the reagents and consumables used in this application are commercially available.
[0048] According to a first aspect of the present application, a retarder for potassium magnesium phosphate gelling material is provided, wherein the retarder comprises a compound containing a chelating group.
[0049] The coordinating atom in the chelating group can provide at least one lone pair of electrons, and combine with the metal ion providing the empty orbital by a coordination bond.
[0050] The raw material of potassium magnesium phosphate cementitious material is used as a rapid filling and repair material, and its early strength is high, but its setting time is too short to meet the requirements of normal construction operations. The present application prolongs the setting time of potassium magnesium phosphate cementitious material by adding a retarder raw material containing a chelating group to the raw material of potassium magnesium phosphate cementitious material, and at the same time ensures the strength of the potassium magnesium phosphate cementitious material after setting, so that the repaired structure can be restored to use within a short period of time after repair.
[0051] Preferably, the chelating group may include a neutral group, and the neutral group may include an amino group. Hydroxyl Azo and thiol groups At least one of; and / or the chelating group may include a negative ion, the negative ion may include a carboxyl group Phenol Phosphate and urea At least one of .
[0052] Preferably, the chelating group may include at least one of a hydroxyl group, a thiol group, a urea group and a phosphate group.
[0053] Preferably, the hydroxyl group can be provided by a hydroxyl type compound, and the hydroxyl type compound includes citric acid tartaric acid Gluconic acid Aminotrimethylenephosphonic acid Hydroxyethylenediphosphonic acid and pyrosulfate Preferably, the pyrosulfate is used. The atom R in the pyrosulfate may be a metal ion, such as potassium and sodium, and preferably sodium pyrosulfate. The sodium pyrosulfate is in the form of colorless crystal particles, and its purity is ≥98% by mass.
[0054] Preferably, the thiol group is provided by a thiol-type compound, and the thiol-type compound includes dithiocarbamate Dipotassium dithiocarbamate Aminodithiocarbamate chelating resin and thiourea At least one of; and / or the urea group is provided by a urea-based compound, the urea-based compound comprising urea and thiourea At least one of the above thiol-based compound and / or urea-based compound is preferably thiourea. The above thiourea is in the form of colorless crystalline particles, and its purity is ≥99% by mass percentage.
[0055] Preferably, the phosphate group can be provided by a phosphate-based compound, which can include an inorganic polyphosphate-based compound. Triphosphate and pyrophosphate Preferably, it is pyrophosphate, in which the atom R can be a metal ion, such as potassium and sodium, and preferably sodium pyrophosphate. The sodium pyrophosphate is a white solid powder, and its purity is ≥99% by mass percentage.
[0056] According to the second aspect of the present application, a raw material for potassium magnesium phosphate gelling material is proposed, and the raw material for the potassium magnesium phosphate gelling material includes magnesium oxide, potassium dihydrogen phosphate and a retarder, and the retarder is the above-mentioned retarder.
[0057] The magnesium oxide can be prepared in an appropriate manner, for example, it can be dead-burned magnesium oxide prepared by calcining magnesite at 1700° C. for 1-4 hours, and the purity of the potassium dihydrogen phosphate is ≥ 99%. The dead-burned magnesium oxide has a high purity, so that the potassium magnesium phosphate cementitious material prepared with the dead-burned magnesium oxide as a raw material has a higher strength.
[0058] Preferably, the raw materials of the potassium magnesium phosphate gelling material include 100-500 parts of magnesium oxide, 100-300 parts of potassium dihydrogen phosphate and 3-50 parts of retarder, in parts by weight.
[0059] Preferably, the raw materials of the potassium magnesium phosphate gelling material include 200-450 parts of magnesium oxide, 125-250 parts of potassium dihydrogen phosphate and 8-36 parts of retarder, in parts by weight.
[0060] Preferably, the raw materials of the potassium magnesium phosphate gelling material include 250-350 parts of magnesium oxide, 150-200 parts of potassium dihydrogen phosphate and 10-21 parts of retarder, in parts by weight.
[0061] The retarder is one of sodium pyrophosphate, sodium pyrosulfate and thiourea. In different engineering operations, different setting times of potassium magnesium phosphate cementitious materials are required. Therefore, one of the retarders can be selected according to different application scenarios.
[0062] According to the third aspect of the present application, a potassium magnesium phosphate gelling material is proposed, which includes raw materials of potassium magnesium phosphate gelling material and water. By weight, it can include 180 parts to 240 parts of raw materials of potassium magnesium phosphate gelling material and 60 parts to 120 parts of water. The raw materials of the potassium magnesium phosphate gelling material are the raw materials of the above-mentioned potassium magnesium phosphate gelling material.
[0063] Preferably, in an air-hardening environment, the setting time of the potassium magnesium phosphate cementitious material is at least 8 minutes, the compressive strength of the potassium magnesium phosphate cementitious material after 3 days of setting is at least 20 MPa, the compressive strength after 28 days of setting is at least 40 MPa, and the flexural strength is at least 6 MPa.
[0064] The above-mentioned gas-hardening environment is an environment in which a material gradually hardens at normal atmospheric temperature and has considerable strength.
[0065] Example 1
[0066] The raw materials of potassium magnesium phosphate gelling material include, by weight, 100 parts of magnesium oxide, 100 parts of potassium dihydrogen phosphate and 3 parts of retarder. The potassium magnesium phosphate gelling material includes, by weight, 60 parts of water, 180 parts of potassium magnesium phosphate raw materials, and the addition amount of retarder is 3% (relative to magnesium oxide).
[0067] Example 2
[0068] The raw materials of the potassium magnesium phosphate gelling material include, by weight, 500 parts of magnesium oxide, 300 parts of potassium dihydrogen phosphate and 50 parts of retarder. The potassium magnesium phosphate gelling material includes, by weight, 120 parts of water, 240 parts of potassium magnesium phosphate raw materials, and 10% of the retarder (relative to magnesium oxide).
[0069] Example 3
[0070] The raw materials of potassium magnesium phosphate gelling material are, by weight, 200 parts of magnesium oxide, 125 parts of potassium dihydrogen phosphate and 8 parts of retarder. The potassium magnesium phosphate gelling material includes, by weight, 90 parts of water and 210 parts of potassium magnesium phosphate raw materials. The amount of retarder added is 4% (relative to magnesium oxide).
[0071] Example 4
[0072] The raw materials of potassium magnesium phosphate gelling material are, by weight, 450 parts of magnesium oxide, 250 parts of potassium dihydrogen phosphate and 36 parts of retarder. The potassium magnesium phosphate gelling material includes, by weight, 120 parts of water and 180 parts of potassium magnesium phosphate raw materials. The amount of retarder added is 8% (relative to magnesium oxide).
[0073] Example 5
[0074] The raw materials of potassium magnesium phosphate gelling material are, by weight, 250 parts of magnesium oxide, 150 parts of potassium dihydrogen phosphate and 10 parts of retarder. The addition amount of each component in the potassium magnesium phosphate gelling material is the same as that in Example 1, and the addition amount of the retarder is 4% (relative to magnesium oxide).
[0075] Example 6
[0076] The raw materials of potassium magnesium phosphate gelling material are, by weight, 350 parts of magnesium oxide, 200 parts of potassium dihydrogen phosphate and 21 parts of retarder. The addition amount of each component in the potassium magnesium phosphate gelling material is the same as that in Example 2, and the addition amount of the retarder is 6% (relative to magnesium oxide).
[0077] Example 7
[0078] The raw materials of potassium magnesium phosphate gelling material are, by weight, 300 parts of magnesium oxide, 200 parts of potassium dihydrogen phosphate and 26.5 parts of retarder. The addition amount of each component in the potassium magnesium phosphate gelling material is the same as that in Example 4, and the addition amount of the retarder is 8.83% (relative to magnesium oxide).
[0079] Example 8
[0080] The raw materials of potassium magnesium phosphate gelling material are, by weight, 325 parts of magnesium oxide, 175 parts of potassium dihydrogen phosphate and 22 parts of retarder. The addition amount of each component in the potassium magnesium phosphate gelling material is the same as that in Example 3, and the addition amount of the retarder is 6.77% (relative to magnesium oxide).
[0081] Comparative Example 1
[0082] The raw material composition and addition amount of the potassium magnesium phosphate gelling material and the addition amount of each component in the potassium magnesium phosphate gelling material are the same as those in Example 2, wherein the retarder is borax, and the addition amount of borax is 10% (relative to magnesium oxide).
[0083] Comparative Example 2
[0084] The raw material composition and addition amount of the potassium magnesium phosphate gelling material and the addition amount of each component in the potassium magnesium phosphate gelling material are the same as those in Example 3, wherein the retarder is borax, and the addition amount of borax is 4% (relative to magnesium oxide).
[0085] Comparative Example 3
[0086] The raw material composition and addition amount of the potassium magnesium phosphate gelling material and the addition amount of each component in the potassium magnesium phosphate gelling material are the same as those in Example 4, wherein the retarder is borax, and the addition amount of borax is 8% (relative to magnesium oxide).
[0087] Comparative Example 4
[0088] The raw material composition and addition amount of the potassium magnesium phosphate gelling material and the addition amount of each component in the potassium magnesium phosphate gelling material are the same as those in Example 6, wherein the retarder is borax, and the addition amount of borax is 6% (relative to magnesium oxide).
[0089] 2. Preparation method of potassium magnesium phosphate gelling material
[0090] A method for preparing a potassium magnesium phosphate gelling material, the preparation method comprising:
[0091] S1. Magnesium oxide (Liaoning Haicheng Xuefeng Magnesium Industry Co., Ltd.) and potassium dihydrogen phosphate (Sichuan Anda Nongsen Technology Co., Ltd.) were weighed respectively according to weight parts, and mixed to obtain potassium magnesium phosphate raw material.
[0092] S2. Weigh sodium pyrophosphate (Shanghai McLean Biochemical Technology Co., Ltd.), sodium pyrosulfate (Shanghai McLean Biochemical Technology Co., Ltd.) or thiourea (Shanghai McLean Biochemical Technology Co., Ltd.) according to weight, and dissolve it in water to form a retarder solution.
[0093] S3. Add the potassium magnesium phosphate raw material of S1 to the composite retarder solution obtained in S2 to prepare a potassium magnesium phosphate gelling material slurry.
[0094] S4. Pour the above potassium magnesium phosphate cementitious material into a mold, vibrate it on a cement mortar vibrating table, demould it and place it in a constant temperature and humidity environment, and cure it for 3 days, 7 days, 14 days and 28 days respectively to obtain the potassium magnesium phosphate cementitious material. The curing conditions are a temperature of 23°C-26°C and a relative humidity of 58%-68%.
[0095] The above steps may also be performed by weighing magnesium oxide and potassium dihydrogen phosphate, and then weighing sodium pyrophosphate, sodium pyrosulfate or thiourea, respectively, mixing them evenly, and then adding water to dissolve them to prepare the potassium magnesium phosphate gelling material.
[0096] It should be noted that the above preparation method is not limited to the steps described in this application, and other appropriate steps may also be used. The potassium magnesium phosphate gelling material of the comparative example is also prepared according to the above method.
[0097] 3. Analysis of the principle of retarder delaying the setting time of potassium magnesium phosphate cementitious material
[0098] 3.1 Activity analysis of dead-burned magnesium oxide
[0099] 1. Dissolution of dead-burned magnesium oxide H dissolved in water + Protonated, basic oxides of MgO act as electron donors.
[0100] MgO (S) +H2O (L) →MgOH + (Surface) +OH -(aq)
[0101] 2.OH - Electrostatically adsorbed to MgOH + surface.
[0102] MgOH + (Surface) +OH - (aq) →MgOH + OH - (Surface)
[0103] 3. Mg 2+ and OH - It is released into the liquid medium until its concentration reaches saturation, and finally magnesium hydroxide precipitate is generated.
[0104] MgOH + OH - (Surface) →Mg 2+ (aq) +OH - (aq)
[0105] Mg 2+ (aq) +OH - (aq) →Mg(OH) 2(S)
[0106] 4. Performance test of dead burned magnesium oxide
[0107] The performance test of dead-burned magnesium oxide may be an appropriate method, and the acetic acid method is used in this application. Figure 1 It can be seen that the time it takes for the dead-burned magnesium oxide to react with acetic acid (Tianjin Yongda Chemical Reagent Co., Ltd.; purity 99.5%) to reach a pH of 7 is 165 minutes, indicating that the dead-burned magnesium oxide has a relatively low activity.
[0108] 3.2 Analysis of dissolution, dispersion, bonding and crystallization mechanism of raw materials of potassium magnesium phosphate cementitious materials
[0109] The main theoretical reaction equation of potassium magnesium phosphate gelling material is:
[0110] MgO+KH2PO4+5H2O→MgKPO4·6H2O
[0111] 1. Potassium dihydrogen phosphate dissolves in aqueous solution, releasing K + , H + 、H2PO4 - 、HPO4 2- PO4 3-.
[0112] 2. If Figure 2 As shown in a, the acidic ions in the solution will have an "attractive" effect to promote the dissolution of magnesium oxide particles.
[0113] 3. Such as Figure 2 As shown in b, the ionic groups (hydrated magnesium ions) diffuse until they reach a saturated state, which is called a hydrosol, after which an acid-base neutralization reaction occurs ( Figure 2 c) in.
[0114] 4. Such as Figure 2 As shown in (d), as the reaction temperature increases, the hydration reaction rate accelerates and more hydrogels are formed. As the crystal nuclei of the hydration products continue to be produced, grow, contact and connect with each other, a tightly connected hydrogel is generated.
[0115] 5. As Figure 2 As shown in e, the unreacted magnesium oxide is used as a filler, and the final hydration product is a binder, forming a tightly structured crystalline network structure, which can give the potassium magnesium phosphate cementitious material special properties.
[0116] 3.3 Mechanism of action of retarder for potassium magnesium phosphate cementitious materials
[0117] 1. Protective film theory: the retarder provides coordinated atoms, which react with magnesium ions through coordination bonds to form a compound protective film or complex, which hinders the reaction between magnesium ions and phosphate.
[0118] 2. Change the pH value of the system. By increasing the pH value of the liquid phase, the dissolution of ions can be inhibited and the hydration reaction can be delayed.
[0119] Theoretical equation of chelation reaction:
[0120] Chelating agents (n-) +Mg 2+ →Mg n Chelating agent 2 (insoluble matter)
[0121] Chelating agents (n-) +MgOH + →MgOH + Chelating agents (n-)
[0122] Magnesium ions react with the retarder to form chelates that cover the surface of the undissolved magnesium oxide particles, occupying the position of phosphate ions in the liquid phase, forming a protective film that hinders the contact between phosphate and other acid ions in the reaction system and magnesium oxide, slowing down the reaction rate of the system, and thus reducing the hydration heat. The continuous accumulation of phosphate ions will form osmotic pressure in the protective layer on the surface of the magnesium oxide particles. As the reaction time continues to pass, the phosphate ions will penetrate into the protective film and then contact the surface of magnesium oxide, thereby forming MgKPO4·6H2O on the surface of magnesium oxide.
[0123] 4. Experimental Results
[0124] 4.1 Mechanical properties
[0125] 4.1.1 Flexural strength
[0126] Figure 3-Figure 5 When the retarder in Examples 1-8 is sodium pyrophosphate, sodium pyrosulfate and thiourea respectively, the flexural strength of the potassium magnesium phosphate cementitious material after 3d, 7d, 14d and 28d of preparation, Figure 6 The flexural strength of Comparative Examples 1-4 after 3d, 7d, 14d and 28d of preparation. Figure 3 It can be seen that when the retarder is sodium pyrophosphate, the flexural strength of Examples 1, 3, 5, 6 and 8 after 3 days of preparation reaches more than 6 MPa. Figure 4 It can be seen that when the retarder is sodium pyrosulfate, the flexural strength of Example 3 after 3 days of preparation reaches more than 6MPa. Figure 5 It can be seen that when the retarder is thiourea, the flexural strength of Examples 3 and 5 after 3 days of preparation reaches more than 6 MPa. Among them, when the retarder is sodium pyrophosphate, sodium pyrosulfate or thiourea, the flexural strength of Example 3 is the highest. Figure 6 It can be seen that the flexural strength of the potassium magnesium phosphate gelling materials of Comparative Examples 2 and 4 also reached above 6 MPa after 3 days of preparation.
[0127] 4.1.2 Compressive strength
[0128] Figure 7-Figure 9 When the retarder in Examples 1-8 is sodium pyrophosphate, sodium pyrosulfate and thiourea respectively, the compressive strength of the potassium magnesium phosphate cementitious material after 3d, 7d, 14d and 28d of preparation, Fig.10 The compressive strength of Comparative Examples 1-4 after 3d, 7d, 14d and 28d of preparation. Figure 7-10 As shown in Figure 2, the compressive strength of the potassium magnesium phosphate cementitious materials of Examples 1-8 and Comparative Examples 1-4 reached above 20 MPa after 3 days of preparation. Figure 7As shown, when the retarder is sodium pyrophosphate, the compressive strength of the potassium magnesium phosphate cementitious materials of Examples 1-8 all reaches above 40 MPa; when the retarder is sodium pyrosulfate, the compressive strength of the potassium magnesium phosphate cementitious materials of Examples 1 and 3 reaches above 40 MPa; when the retarder is thiourea, the compressive strength of the potassium magnesium phosphate cementitious materials of Examples 1, 3 and 5 reaches above 40 MPa; among them, when the retarder is sodium pyrophosphate, sodium pyrosulfate or thiourea, the compressive strength of Example 3 is the highest, Fig.10 It can be seen that the compressive strength of the potassium magnesium phosphate cementitious materials of Comparative Examples 2 and 4 reaches above 40 MPa.
[0129] 4.2 Setting time
[0130] Figure 11-13 When the retarder in Examples 1-8 is sodium pyrophosphate, sodium pyrosulfate and thiourea, respectively, the setting time of potassium magnesium phosphate gelling material is: Fig.10 is the setting time of potassium magnesium phosphate gelling materials of comparative examples 1-4. Figure 11-Figure 14 It can be seen that the setting time of potassium magnesium phosphate gelling materials in Comparative Examples 1-4 and Examples 1-8 is more than 10 minutes. Fig.11 When the retarder is sodium pyrophosphate, the setting time of potassium magnesium phosphate cementitious materials is greater than 13 minutes. Fig.12 It can be seen that when the retarder is sodium pyrosulfate, the setting time of potassium magnesium phosphate cementitious materials is greater than 11 minutes. Fig.13 It can be seen that when the retarder is thiourea, the setting time of potassium magnesium phosphate cementitious materials is greater than 12 minutes. Fig.14 Among them, the setting time of potassium magnesium phosphate gelling materials of Comparative Examples 1-4 is greater than 14 minutes.
[0131] 4.3 Microstructure
[0132] Combining the flexural strength and the setting time, among Examples 1-8, Example 3 has the highest flexural strength and compressive strength. When the retarder is sodium pyrophosphate, the setting time of the potassium magnesium phosphate cementitious material of Example 3 is greater than 14 min. When the retarder is sodium pyrosulfate, the setting time of the potassium magnesium phosphate cementitious material of Example 3 is greater than 11 min. When the retarder is thiourea, the setting time of the potassium magnesium phosphate cementitious material of Example 3 is greater than 12 min. In order to meet the different requirements of the setting time of potassium magnesium phosphate cementitious materials in different application scenarios and ensure their flexural strength and compressive strength, sodium pyrophosphate, sodium pyrosulfate and thiourea are prepared according to Example 3 respectively, which can meet the requirements of the flexural strength and compressive strength of potassium magnesium phosphate cementitious materials, and their setting time can also meet different application scenarios. For example, in highway engineering repairs, the setting time of the potassium magnesium phosphate cementitious materials used is relatively long, and sodium pyrophosphate can be selected as a retarder. However, in the facade repair of subway prefabricated pipe segments, the required setting time of the potassium magnesium phosphate cementitious materials is relatively short, and sodium pyrosulfate or thiourea can be selected as a retarder.
[0133] In the comparative examples, in combination with the flexural strength and setting time, the setting time, flexural strength after setting and compressive strength of comparative examples 2 and 4 are more suitable.
[0134] In the present application, the microstructures of Example 3 and Comparative Example 4 were detected respectively. Figure 15-17 The microstructures of potassium magnesium phosphate gelling materials in Example 3 when the retarder is sodium pyrophosphate, sodium pyrosulfate and thiourea, respectively. Fig.18 It is the microstructure of comparative example 4. Figure 15-18 It can be seen that the potassium magnesium phosphate cementitious materials of Example 3 and Comparative Example 4 have neatly arranged structures after solidification and a high degree of compactness. The structure affects the performance, and the mechanical strength becomes correspondingly higher.
[0135] In summary, the retarder of the present application can delay the setting time of the potassium magnesium phosphate cementitious material as needed, while ensuring the flexural and compressive strengths of the potassium magnesium phosphate cementitious material after setting, and can adapt to different engineering application scenarios.
[0136] When the amount of the retarder added in the present application is small (3-4%), the retarder in the reaction system mainly undergoes an ionization reaction, and the reaction process is dominated by a chelation reaction. The chelate groups ionized by the novel retarder will undergo a chelation reaction with magnesium ions; when the amount of the retarder added is large (higher than 4%), the retarder in the reaction system mainly undergoes a hydrolysis reaction, and the pH adjustment of the hydration process is dominant. In the reaction system, the retarder will not only ionize the chelate groups to undergo a chelation reaction with magnesium ions, but also undergo a hydrolysis reaction. In the hydrolysis process, H + With SO4 2-The formation of retarder reduces the hydration pH value, causing the amount of hydration products and microstructure to change, resulting in negative changes in performance. In other words, when the addition amount is small, sodium pyrophosphate, thiourea or sodium pyrosulfate can increase the liquid phase pH value, while when the addition amount is too high, it will reduce the hydration pH value of the system. Therefore, when the addition amount of retarder is 3-4%, the performance is optimal.
[0137] 5. Effect of sodium pyrophosphate on the basic properties of potassium magnesium phosphate cementitious materials:
[0138] The modification of potassium magnesium phosphate cementitious materials with sodium pyrophosphate added in amounts of 4%, 6%, 8%, and 10% was studied. After 28 days of standard curing, the mechanical strength of potassium magnesium phosphate cementitious materials gradually decreased with the increase of sodium pyrophosphate addition (4-10%). When the addition amount was 4%, its compressive strength and flexural strength were 52.7MPa and 8.8MPa, respectively. According to the "Repair Mortar" (JC / T2381-2016), its mechanical strength is much higher than its standard, and its modification effect is better than that of borax added in an amount of 6%. The reason for the continuous decrease in mechanical strength may be that as the content of sodium pyrophosphate in the reaction system continues to increase, the amount of hydration products will decrease, or the newly generated intermediate products affect the structure of the hydration products (MgKPO4·6H2O), so the mechanical strength is constantly decreasing.
[0139] When the addition amount of sodium pyrophosphate increases from 4% to 10%, the strength retention rate of potassium magnesium phosphate cementitious material decreases from 0.986 to 0.940, so the optimal addition amount of sodium pyrophosphate should be 4%. The reason is that with the continuous increase in the addition amount of sodium pyrophosphate, the amount of hydration products inside it will continue to decrease. After immersion curing, the structure of the hydration products will dissolve and decompose, which will lead to a continuous decrease in strength retention rate and a decrease in water resistance.
[0140] When the addition amount of sodium pyrophosphate increased from 4% to 10%, the hydration pH value decreased from 12.23 to 11.96 in the final relatively stable stage. Fig.19 (a) is the hydration pH value change diagram of MKPC within 80 minutes. Fig.19 The middle figure (b) shows the change of hydration pH value of MKPC within 360 minutes. Fig.19As can be seen in (a), with the continuous increase in the amount of sodium pyrophosphate added, the hydration time at the inflection point continues to extend and the peak value continues to decrease. When the amount of sodium pyrophosphate added increases from 4% to 10%, at the first inflection point, the conversion time of the intermediate hydration phase MgHPO4·3H2O to Mg2KH(PO4)2·15H2O is delayed from 13min to 28min, and the hydration pH peak value decreases from 7.44 to 7.2; at the second inflection point, the conversion time of the intermediate hydration phase Mg2KH(PO4)2·15H2O to the final hydration product MgKPO4·6H2O is extended from 38min to 45min, and the hydration pH peak value decreases from 9.23 to 8.97. Fig.19 It can be seen from (b) that when the addition amount of sodium pyrophosphate increases from 4% to 10%, the hydration pH value decreases from 12.23 to 11.96 in the final relatively stable stage. Therefore, it is explained that as the content of sodium pyrophosphate increases in the reaction system, the ionized chelate groups will react with the magnesium ions attached to the surface of the dead-burned magnesium oxide particles, inhibiting the further dissolution of the magnesium oxide particles, reducing the hydration pH value of the reaction system, and hindering its reaction with phosphate to a certain extent, resulting in a delay in the hydration reaction rate and a prolonged coagulation time.
[0141] After 28 days of standard curing, the effect of sodium pyrophosphate on the hydration products and reaction degree of potassium magnesium phosphate cementitious materials is shown in Figure 2. Fig. 20 (a) is the mass loss diagram of MKPC; Fig. 20 (b) is a graph showing the amount of hydration products and the degree of reaction of MKPC. The main weight loss temperature range of potassium magnesium phosphate cementitious materials is 50-200°C, and the mass loss is most serious at around 100°C, which is caused by the high-temperature dehydration of the hydration product MgKPO4·6H2O. Fig. 20 As can be seen in (a), with the continuous increase of the amount of sodium pyrophosphate added in the reaction system, the mass loss at 50-200°C shows a decreasing trend, and at 200-800°C, the mass loss first increases and then decreases. The mass loss can be used to analyze the effect of sodium pyrophosphate on the amount of hydration products and the degree of reaction of potassium magnesium phosphate cementitious materials, such as Fig. 20 In (b), it can be seen that when the addition amount of sodium pyrophosphate is 4%, the amount of hydration products and the degree of reaction reach the optimal value, the amount of hydration products is 68.47wt.%, and the reaction degrees of potassium dihydrogen phosphate and magnesium oxide are 45.49% and 12.12%, respectively. The modification mechanism of sodium pyrophosphate in the reaction system can be divided into two theoretical models, namely the protective film theory and the hydration pH adjustment theory. The explanation for the protective film theory is that sodium pyrophosphate in the reaction system reacts with the Mg on the surface of the dead-burned magnesium oxide particles through the ionized chelating groups. 2+The reaction forms a chelate, which prevents phosphate from reacting with it. The theoretical explanation for adjusting the hydration pH is that, since sodium pyrophosphate is an alkaline compound, as the amount added increases, it promotes the dissolution of potassium dihydrogen phosphate and increases the osmotic pressure on both sides of the protective membrane, causing hydrogen ions and phosphates to penetrate into the inner side of the protective membrane at an accelerated rate. Since C3S exists in the dead-burned magnesium oxide particles, as the hydration reaction continues, phosphates will react with calcium ions on the surface of the dead-burned magnesium oxide particles to form calcium phosphate, which increases the degree of reaction between potassium dihydrogen phosphate and magnesium oxide. However, in an environment with a lower hydration pH value, it is not conducive to the formation of hydration products, so the amount of hydration products continues to decrease.
[0142] After 28 days of standard curing, the effect of different addition amounts of sodium pyrophosphate on the phase composition of potassium magnesium phosphate cementitious material. Fig.21 It can be seen that the main phases in MKPC after sodium pyrophosphate modification are the hydration product MgKPO4·6H2O and residual magnesium oxide. With the continuous increase in the amount of sodium pyrophosphate added, the diffraction peak intensity of the hydration product shows a decreasing trend as a whole, and the crystallinity of the hydration product continues to decrease, resulting in a continuous decrease in performance. Therefore, the optimal addition amount is 4%. When the amount of sodium pyrophosphate added is large, it can be observed that there is still a small amount of calcium phosphate in the reaction system, which can be mutually verified with the above experimental conclusions. Excessive sodium pyrophosphate can increase the degree of reaction in MKPC and reduce the hydration pH value in the reaction system, which is not conducive to the stable existence of the hydration product, resulting in a continuous decrease in the amount of hydration product generated.
[0143] Depend on Fig. 22 It can be seen that after 28 days of standard curing, the microstructure of the modified material was characterized by SEM. When the addition amount of sodium pyrophosphate increased from 4% to 8%, it can be clearly observed that its main microscopic morphology is a plate-like or prismatic structure, but the smoothness of the surface of the hydration product, the density and integrity of the structure are constantly decreasing. When the addition amount is 4%, it can be clearly found that the plate-like structure of the hydration product is tightly stacked, orderly arranged and has high crystallinity, so the comprehensive performance is the best. When the addition amount increases to 10%, it can be seen that its main microscopic morphology is amorphous particle accumulation. As the addition amount of sodium pyrophosphate continues to increase, the hydration pH value will continue to decrease, which is not conducive to the formation of hydration products, and in a reaction environment with a lower pH, the hydration product is prone to dissolution, destroying the microscopic morphology, reducing the crystallinity, and reducing performance.
[0144] According to the above performance test results, the modification effects of 4% sodium pyrophosphate and 6% borax on MKPC are compared, and the former is more excellent. Fig.23 The pore structure of MKPC modified by adding 4% sodium pyrophosphate and 6% traditional retarder borax after 28 days of standard curing is shown. Fig.23 In the pore size distribution diagram (a), it can be seen that in the range of pore size greater than 200 nm, the peak value of MKPC modified with 6% borax is the highest, and in the range of pore size less than 10 nm, the peak value of MKPC modified with 4% sodium pyrophosphate is slightly lower; Fig.23 In the cumulative pore volume graph (b), it can be seen that the cumulative pore volume curve after borax modification increases greatly in the pore size range greater than 200 nm, while the cumulative pore volume curve after sodium pyrophosphate modification increases less in the pore size range less than 10 nm. Fig.23 In (c), it can be concluded that in the range of pore size greater than 200 nm, the pore volume after modification with 4% sodium pyrophosphate accounts for 37.04%, while the pore volume after modification with 6% borax accounts for 47.85%. This shows that after sodium pyrophosphate modification, the phosphate in the MKPC hardener has fully reacted, generating a large amount of hydration products to fill the macroporous structure.
[0145] 6. Effect of thiourea on the basic properties of potassium magnesium phosphate cementitious materials
[0146] When the addition amount increases from 4% to 10%, the setting time is correspondingly extended from 12.22min to 16.48min, and the setting time is controlled at more than 10min, which can also meet most engineering requirements. The retarding mechanism may be due to the fact that the anionic chelating groups ionized by thiourea react with magnesium ions in the reaction system to form chelates. The reaction process is similar to the effect of sodium pyrophosphate, thereby inhibiting the dissolution of dead-burned magnesium oxide to achieve the effect of slowing down the reaction rate. Under the same curing age, with the increase of thiourea addition (4% to 10%), the mechanical strength of potassium magnesium phosphate cementitious material gradually decreases, and its change trend is similar to the change trend of the effect of sodium pyrophosphate on the mechanical strength of MKPC. Based on the addition amount of thiourea of 4%, after 28 days of standard curing, the flexural strength and compressive strength of MKPC reached 6.7MPa and 39.8MPa respectively, which are also better than the "Repair Mortar" (JC / T 2381-2016) standard. The reasons for the continuous decrease in mechanical strength are similar to the effects of sodium pyrophosphate, which may be due to the reduction of the reaction degree by thiourea or the influence of intermediate by-products on the reaction products, resulting in a decrease in the amount of production or structural damage, and the mechanical strength continues to decrease.
[0147] In a water-immersion environment, when the addition amount of thiourea increases from 4% to 10%, the strength retention rate of potassium magnesium phosphate cementitious material decreases from 0.943 to 0.879, and the optimal addition amount is 4%. The reason is that with the increase in the addition amount of thiourea, the amount of hydration products gradually decreases. In a water-immersion environment, water will enter the structure through the pores, weakening the binding force between the hydration products and dissolving the contact points of the crystals, causing the structure to be destroyed and the water resistance to decrease.
[0148] like Fig.24 As shown in the figure, when the addition amount of thiourea increases from 4% to 10%, the hydration pH drops from 11.81 to 11.63 in the final stable stage. This shows that thiourea also inhibits the precipitation formation process of the intermediate hydration phase and MgKPO4·6H2O, and also slows down the conversion rate of the intermediate hydration phase to MgKPO4·6H2O. As the thiourea content in the reaction system increases, the chelating groups in the reaction system will react with the magnesium ions on the surface of the dead-burned magnesium oxide particles to form chelates attached to the particle surface, which hinders the direct reaction of magnesium ions with phosphates, slows down the dissolution rate of magnesium oxide particles, delays the hydration reaction rate, and reduces the hydration pH value.
[0149] Fig.25 The effect of thiourea on the hydration products and reaction degree of potassium magnesium phosphate cementitious materials after 28 days of standard curing. Fig.25 (a) is the mass loss diagram of MKPC; Fig.25 (b) shows the amount of hydration products and the degree of reaction of MKPC. The thermogravimetric curve is consistent with the typical thermogravimetric curve of potassium magnesium phosphate gelling material. Fig.25 As can be seen in (a), with the continuous increase of thiourea addition, the mass loss at 50-200°C shows a decreasing trend, and at 200-800°C the mass loss first increases and then decreases. Fig.25 As shown in (b), when the addition amount of thiourea is 4%, the amount of hydration product and the degree of reaction both reach the highest value, the amount of hydration product is 58.01wt.%, and the degree of reaction of potassium dihydrogen phosphate and magnesium oxide are 33.52% and 8.93%, respectively. Fig.25The change trend of (b) in the reaction system can be summarized as the protective film theory and the hydration pH adjustment theory. The mechanism of action is similar to that of sodium pyrophosphate. The protective film theory can be explained as follows: in the reaction system, the chelating groups ionized from thiourea react with the magnesium ions on the surface of the dead-burned magnesium oxide particles to form a chelate, which slows down the reaction rate and reduces the amount of hydration products. The theoretical explanation for adjusting the hydration pH is that thiourea will also undergo hydrolysis in the reaction system to form magnesium sulfide and aminocyanide. In an alkaline environment, Magnesium sulfide can be converted into magnesium sulfate after oxidation, and cyanamide can be converted into urea. Since urea is a weakly alkaline compound, it will promote the dissolution of residual potassium dihydrogen phosphate in the reaction system, reduce the hydration pH value, and increase the ion osmotic pressure on both sides of the protective membrane. Phosphate will penetrate into the inner side of the protective membrane, stimulating the accelerated dissolution of the dead-burned magnesium oxide particles and increasing the degree of reaction. At the same time, urea can ionize chelating groups, which can directly or indirectly hinder the formation of hydration products. In an environment with a lower hydration pH value, it is not conducive to the formation of hydration products, and the amount of hydration products generated is reduced.
[0150] like Fig.26 As shown in the figure, the XRD diffraction spectrum was used to analyze the effect of different addition amounts of thiourea on the phase composition of potassium magnesium phosphate cementitious material after 28 days of standard curing. It can be seen from the figure that the main phases in MKPC after thiourea modification are hydration product MgKPO4·6H2O and residual magnesium oxide. With the continuous increase of the addition amount, the diffraction peak intensity of the hydration product MgKPO4·6H2O is also decreasing, the crystallinity is continuously decreasing, and the performance is continuously decreasing, which can be mutually verified with the above experimental results. The optimal addition amount is 4%. As for the calcium phosphate and magnesium sulfate tetrahydrate appearing in the reaction system, they are both by-products produced during the reaction process, and their diffraction peak intensity increases with the increase of the thiourea content. This shows that thiourea undergoes a hydrolysis reaction in the reaction system, reduces the pH of the hydration process, slows down the reaction rate of MKPC, and reduces the amount of hydration products generated.
[0151] Fig. 27In order to characterize the microstructure of potassium magnesium phosphate cementitious materials modified with different addition amounts of thiourea after 28 days of standard curing by SEM. When the addition amount of thiourea increases from 4% to 10%, it can be clearly observed that the main microscopic morphology of the hydration product is a stacked plate structure, and the smoothness and crystallinity of the surface change. When the addition amount is too high, it can be clearly observed that there are obvious cracks on the surface of the plate structure and the structural integrity is poor. It can be explained that the hydration product is damaged by the influence of the crystallization pressure in the environment of low hydration pH. At the same time, it is observed that the amorphous flocculent particles on the surface of the hydration product are increasing. From the above XRD diffraction spectrum, it can be seen that this particle flocculent may be magnesium sulfate tetrahydrate and calcium phosphate generated during the hydration reaction. Therefore, the test results and characterization analysis can verify each other, proving that with the increase of thiourea addition, the mechanical properties are constantly decreasing.
[0152] Fig.28 The pore structure comparison diagram of MKPC modified by adding 4% thiourea and 6% borax respectively after 28 days of standard curing is shown. The comprehensive performance improvement of potassium magnesium phosphate cementitious materials is mainly achieved by reducing the number of pores with a pore size greater than 200nm. Fig.28 It can be seen from (a) and (b) that in the range of pore size greater than 1000nm, the number of pores in MKPC after modification with 4% thiourea is higher than that after modification with 6% borax. In the range of 100-200nm, the cumulative pore volume curve of MKPC after modification with 4% thiourea increases greatly, which indicates that there are more pores in the material. It can be concluded from Figure 28 (c) that the volume of pores with a pore size greater than 200nm in MKPC after modification with 4% thiourea accounts for 52.59%, which is larger than the corresponding volume of pores in MKPC after modification with 6% borax. The volume of pores in the range of pore size less than 10nm accounts for 15.83%, which is slightly lower than that after modification with 6% borax. It can be inferred that after modification with 4% thiourea, the amount of hydration products in the pore size range of MKPC less than 10nm is small, and the reaction rate is fast. A large amount of reaction heat is released during the reaction, resulting in a large proportion of pore volume with a pore size greater than 200nm, and a decrease in the overall performance.
[0153] It can be concluded that the performance of MKPC modified with 4% thiourea is slightly lower than that with 6% borax.
[0154] 7. Sodium pyrosulfate modified potassium magnesium phosphate gelling material.
[0155] The potassium magnesium phosphate gelling material was modified by using 4%, 6%, 8% and 10% sodium pyrosulfate:
[0156] The retarding mechanism of sodium pyrosulfate is similar to the mechanism of action of sodium pyrophosphate and thiourea mentioned above. The chelating groups ionized from sodium pyrosulfate in the reaction system react with the magnesium ions on the surface of the dead-burned magnesium oxide particles to stabilize the Mg in the liquid phase. 2+ It hinders the formation of reaction products to slow down the reaction rate and prolong the setting time. After 28 days of standard curing, when 4%, 6%, 8%, and 10% sodium pyrosulfate were used to modify the potassium magnesium phosphate cementitious material, the mechanical strength of MKPC gradually decreased with the increase of sodium pyrosulfate addition. When the addition of sodium pyrosulfate was 4%, its compressive strength and flexural strength were 37.5MPa and 6.3MPa respectively.
[0157] In a water-immersion environment, as the addition amount continues to increase (4%-10%), the strength retention rate of potassium magnesium phosphate cementitious material decreases from 0.926 to 0.831, so the optimal addition amount is 4%. The reason is that as the content of sodium pyrosulfate continues to increase in the reaction system, the amount of hydration products inside it continues to decrease. After immersion and curing, the hydration products will dissolve and decompose, resulting in a continuous decrease in strength retention rate and a decrease in water resistance.
[0158] With the continuous increase of sodium pyrosulfate addition, the hydration time at the inflection point is constantly prolonged and the peak value is constantly decreasing. When the addition amount increases from 4% to 10%, at the first inflection point, the precipitation transformation time of the intermediate hydration phase MgHPO4·3H2O to Mg2KH(PO4)2·15H2O is delayed from 6min to 12min, and the hydration pH peak is reduced from 7.27 to 7.13; at the second inflection point, the precipitation transformation time of the intermediate hydration phase Mg2KH(PO4)2·15H2O to the final hydration product MgKPO4·6H2O is extended from 15min to 23min, and the hydration pH peak is reduced from 8.78 to 8.18. With the increase of addition amount, the hydration pH in the final stable stage decreases from 11.69 to 11.42. This shows that sodium pyrosulfate has a certain delaying effect on the hydration process of MKPC, and can also inhibit the intermediate hydration phase and slow down the precipitation transformation process to the final product. As the amount added in the reaction system continues to increase, a large number of ionized chelating groups will react with the magnesium ions attached to the surface of the dead-burned magnesium oxide particles to chelate, slowing down the dissolution of the magnesium oxide particles, reducing the hydration pH value, delaying the hydration reaction rate, and prolonging the coagulation time.
[0159] As the addition amount of sodium pyrosulfate increases, the mass loss at 50-200°C decreases, and the mass loss at 200-800°C increases first and then decreases. This allows us to analyze the effect of sodium pyrosulfate on the amount of hydration products and the degree of reaction of MKPC. When the addition amount of sodium pyrosulfate is 4%, the amount of hydration products and the degree of reaction also reach the optimal value, with the amount of hydration products being 55.22wt.%, and the reaction degrees of potassium dihydrogen phosphate and magnesium oxide being 26.09% and 6.95%, respectively. The modification mechanism of sodium pyrosulfate in the reaction system is similar to that of sodium pyrophosphate and thiourea, and can also be summarized as the protective film theory and the hydration pH adjustment theory. The explanation for the protective film theory is that the chelating groups ionized by sodium pyrosulfate in the reaction system will react with the Mg on the surface of the dead-burned magnesium oxide particles. 2+ The reaction generates a chelate, forming a protective film that hinders the formation of hydration products. The theoretical explanation for adjusting the hydration pH is that sodium pyrosulfate will hydrolyze H + With SO4 2- In an environment with a lower hydration pH and a higher concentration of sulfate, its competitive ability is greater, and it will be adsorbed on the surface of the magnesium oxide particles, slowing down the dissolution rate of magnesium oxide. As the hydration reaction continues, the C3S in the dead-burned magnesium oxide particles continues to hydrolyze, and the calcium ion concentration gradually increases. Since the solubility of calcium phosphate is lower than that of calcium sulfate, precipitation conversion will occur, which promotes the ionization of potassium dihydrogen phosphate and increases the degree of reaction in the hydration system. However, in an environment with a lower hydration pH value, it is not conducive to the formation of hydration products and will damage the microstructure of the hydration products.
[0160] After 28 days of curing under standard conditions, the effect of different addition amounts of sodium pyrosulfate on the phase composition of potassium magnesium phosphate cementitious materials. After modification with sodium pyrosulfate, the main phases in MKPC are still the hydration product MgKPO4·6H2O and residual magnesium oxide, and its change trend is similar to that of the XRD diffraction patterns after modification with sodium pyrophosphate and thiourea, respectively. With the continuous increase of the addition amount of sodium pyrosulfate (4%-10%), the diffraction peak intensity of the main hydration product is constantly decreasing, which can be mutually verified with the above experimental analysis. The diffraction peak intensity of calcium phosphate and MgSO4·6H2O increases with the increase of the content of sodium pyrosulfate. The magnesium sulfate hexahydrate crystals generated during the reaction process can indicate that sodium pyrosulfate undergoes hydrolysis reaction in the reaction system, and the generated sulfate ions can occupy active sites on the surface of the dead-burned magnesium oxide particles, thereby slowing down the reaction rate, prolonging the coagulation time, reducing the hydration pH, and reducing the amount of hydration products generated.
[0161] When the addition amount of sodium pyrosulfate increases from 4% to 6%, it can be clearly observed that the smoothness of the surface of the main hydration product and the density of the structure have changed, and obvious cracks have appeared on the surface of the stacked plate structure. When the addition amount of sodium pyrosulfate increases from 8% to 10%, it can be clearly seen that the degree of damage to the plate structure has intensified and the amorphous flocculent particles have increased. This shows that in an environment with a lower hydration pH value, the microstructure of the hydration product will be damaged. Similarly, due to the generation of calcium phosphate and MgSO4·6H2O, crystallization stress will be generated on the stacked structure, further aggravating the damage to the structure. This verifies the above theoretical analysis and also shows that with the increase in the addition amount of sodium pyrosulfate, its mechanical properties and water resistance are constantly decreasing.
[0162] Fig.29 The pore structure comparison chart after 28 days of standard curing is for modifying MKPC with 4% sodium pyrosulfate and 6% traditional retarder borax. In the range of pore size greater than 200nm, the cumulative pore volume curve of MKPC modified with sodium pyrosulfate increases greatly. It can be concluded from the pore size distribution chart that in the range of pore size greater than 200nm, the peak value of MKPC modified with 4% sodium pyrosulfate is higher than that of 6% borax. Fig.29 In (c), the pore volume percentage in MKPC can be obtained. After modification with 4% sodium pyrosulfate, the pore volume percentage in the range of pore size greater than 200nm is 61.07%, which is higher than the pore structure percentage in MKPC after modification with 6% borax. In the range of pore size less than 10nm, the pore structure percentage in MKPC after modification with 4% sodium pyrosulfate is 19.83%, slightly higher than the pore structure percentage after modification with 6% borax. According to the distribution of pore structure and pore volume percentage, it can be analyzed that there is unreacted phosphate in MKPC after modification with 4% sodium pyrosulfate, which absorbs moisture in the environment during standard curing and dissolves, resulting in a large number of pore structures remaining in the hardened body, so the overall performance is low.
[0163] In summary, the modification effect of 6% borax is better than that of 4% sodium pyrosulfate.
[0164] According to the fifth aspect of the present application, an application of a potassium magnesium phosphate cementitious material is proposed, which is the application of the above-mentioned potassium magnesium phosphate cementitious material in repairing and / or protecting cement concrete material structures. The above-mentioned potassium magnesium phosphate cementitious material is the above-mentioned potassium magnesium phosphate cementitious material.
[0165] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.
[0166] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.
[0167] In addition, the various implementation modes of the present application may be arbitrarily combined, and as long as they do not violate the concept of the present application, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A raw material for potassium magnesium phosphate gelling material, characterized in that: The raw materials of the potassium magnesium phosphate gelling material include 200 parts of dead-burned magnesium oxide, 125 parts of potassium dihydrogen phosphate and 8 parts of retarder by weight; Alternatively, the raw materials of the potassium magnesium phosphate gelling material include 100 parts of dead-burned magnesium oxide, 100 parts of potassium dihydrogen phosphate and 3 parts of retarder, in parts by weight; Alternatively, the raw materials of the potassium magnesium phosphate gelling material include 250 parts of dead-burned magnesium oxide, 150 parts of potassium dihydrogen phosphate and 10 parts of retarder, by weight; The retarder is sodium pyrophosphate, sodium pyrosulfate or thiourea.
2. Potassium magnesium phosphate gelling material, characterized in that: The potassium magnesium phosphate gelling material comprises raw materials of potassium magnesium phosphate gelling material and water, which comprises 180 parts to 240 parts of raw materials of potassium magnesium phosphate gelling material and 60 parts to 120 parts of water in parts by weight. The raw materials of the potassium magnesium phosphate gelling material are the raw materials of the potassium magnesium phosphate gelling material according to claim 1. In an air-hardening environment, the setting time of the potassium magnesium phosphate gelling material is at least 8 minutes, the compressive strength of the potassium magnesium phosphate gelling material after setting for 3 days is at least 20 MPa, the compressive strength after setting for 28 days is at least 40 MPa, and the flexural strength is at least 6 MPa.
3. A method for preparing a potassium magnesium phosphate gelling material, characterized in that: The preparation method comprises: fully mixing the raw materials of potassium magnesium phosphate gelling material with water; or mixing the retarder with water, and then adding magnesium oxide and potassium dihydrogen phosphate and stirring to obtain the potassium magnesium phosphate gelling material, wherein: The raw material of the potassium magnesium phosphate gelling material is the raw material of the potassium magnesium phosphate gelling material according to claim 1, and the retarder is the retarder according to claim 1.
4. An application of potassium magnesium phosphate gelling material, characterized in that: The application is the application of the potassium magnesium phosphate cementitious material in repairing and / or protecting cement concrete material structures, and the potassium magnesium phosphate cementitious material is the potassium magnesium phosphate cementitious material described in claim 2.
Citation Information
Cited By
Magnesium phosphate-based underwater pouring cementing material and preparation method thereof
CN120698717A